Heme on innate immunity and inflammation - Dutra, Fabianno F.; Bozza, Marcelo T. (Frontiers in Pharmacology, 2014)
Heme is an essential molecule expressed ubiquitously all through our tissues. Heme plays major functions in cellular physiology and metabolism as the prosthetic group of diverse proteins. Once released from cells and from hemeproteins free heme causes oxidative damage and inflammation, thus acting as a prototypic damage-associated molecular pattern. In this context, free heme is a critical component of the pathological process of sterile and infectious hemolytic conditions including malaria, hemolytic anemias, ischemia-reperfusion, and hemorrhage. The plasma scavenger proteins hemopexin and albumin reduce heme toxicity and are responsible for transporting free heme to intracellular compartments where it is catabolized by heme-oxygenase enzymes. Upon hemolysis or severe cellular damage the serum capacity to scavenge heme may saturate and increase free heme to sufficient amounts to cause tissue damage in various organs. The mechanism by which heme causes reactive oxygen generation, activation of cells of the innate immune system and cell death are not fully understood. Although heme can directly promote lipid peroxidation by its iron atom, heme can also induce reactive oxygen species generation and production of inflammatory mediators through the activation of selective signaling pathways. Heme activates innate immune cells such as macrophages and neutrophils through activation of innate immune receptors. The importance of these events has been demonstrated in infectious and non-infectious diseases models. In this review, we will discuss the mechanisms behind heme-induced cytotoxicity and inflammation and the consequences of these events on different tissues and diseases.